Implementation of modern technologies in language learning as a basis for the formation of communicative competences : monograph - Morhunova, Nadiia; Levchenko, Iaroslava; Kholodov, Anton; Nikulina, Nelia; Rudenko, Svitlana; Miniailo, Nataliia; Kalashnyk, Oksana; Badyeyeva, Liudmyla; Aitbayeva, Bakyt; Zelinska, Olga; Kazmagambetova, Almagul; Shumeiko, Ludmyla; et al. (Technology Center PC, 2025)
The collective monograph is devoted to revealing the role and prospects for the development of the state's economy through its digital transformation during and after the Russian-Ukrainian war and in the context of the Covid-19 pandemic; determining the impact of digital technologies on the labour market, investment and innovation development of society, the competitiveness of the economy and its place in world rankings; form ing the theoretical, methodological and practical foundations for the development of information and communication technologies on the basis of sustainable economic development management. The collective monograph allows all interested stakeholders, based on the analysis of the integration of European management practices into the digital transformation in Ukraine, to get acquainted with practical recommendations and strategic directions for the further development and modernisation of the digital sector of Ukraine's economy to increase its competitiveness and fully exploit its innovative potential in the international market. The monograph is intended for scientists, teachers, students of higher education institutions, postgraduates, doctoral students, practitioners, representatives of state and local authorities, business, administrative staff of higher education institutions, representatives of civil society, the public and all interested parties. Figures 4, Tables 6, References 193 items. This book contains information obtained from authentic and highly regarded sources. Reasonable efforts have been made to publish reliable data and information, but the author and publisher cannot assume responsibility for the validity of all materials or the consequences of their use. The authors and publishers have attempted to trace the copyright holders of all material reproduced in this publication and apologize to copyright holders if permission to publish in this form has not been obtained. If any copyright material has not been acknowledged please write and let us know so we may rectify in any future reprint. The publisher, the authors and the editors are safe to assume that the advice and information in this book are believed to be true and accurate at the date of publication. Neither the publisher nor the authors or the editors give a warranty, express or implied, with respect to the material contained herein or for any errors or omissions that may have been made. Trademark Notice: product or corporate names may be trademarks or registered trademarks, and are used only for identification and explanation without intent to infringe.
Keywords: educational technologies; foreign language communicative competence; information and communication technologies; foreign language; Ukrainian (for professional purposes); Ukrainian as a foreign language; interper sonal interaction; professional culture; professional communication; terminology; projective-recursive technology; 378.091; 10.15587/978-617-8360-15-3